1959
DOI: 10.1302/0301-620x.41b2.314
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Dislocation of the Hip in Identical Twins

Abstract: 1. Congenital dislocation of the hip in identical twins is reported. 2. The heredity of congenital dislocation of hip is discussed. Studies in twins show that congenital dislocation of hip is probably a hereditary dysplasia of the acetabulum and upper end of the femur, and that external factors play a less important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1960
1960
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…In 4678 opposite sex twins, the relative risk of DDH was 0.13 for males compared to females [ 262 ]. Mirroring has been described in two sets of identical twins [ 263 , 264 ] with DDH; one twin had left DDH and the other right DDH. Both sets also had mirrored strabismus, and thumb sucking was mirrored in one set [ 263 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 4678 opposite sex twins, the relative risk of DDH was 0.13 for males compared to females [ 262 ]. Mirroring has been described in two sets of identical twins [ 263 , 264 ] with DDH; one twin had left DDH and the other right DDH. Both sets also had mirrored strabismus, and thumb sucking was mirrored in one set [ 263 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shallow acetabulum and lax capsule were considered to be the main causes of DDH [6,7]. Several family studies indicated that a considerable genetic component played an important role in the etiology of DDH [8-10]. A genome-wide screening from a large four-generation Japanese family of acetabular dysplasia had revealed a linkage between DDH and a specific region at chromosome 13 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several family studies of CDH have showed that its prevalence was significantly higher in first-degree relatives of probands [ 7 - 9 ]. A study of identical twins indicated hereditary factors are of prime importance in CDH [ 10 ], and a genome-wide screening of a Japanese family with acetabular dysplasia identified a linkage on a limited location of the specific chromosome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%